Revealing the sedative-hypnotic effect of the extracts of herb pair Semen Ziziphi spinosae and Radix Polygalae and related mechanisms through experiments and metabolomics approach - Hong Luo; Sheng-jie Sun; Yan Wang; Ying-li Wang (BMC, 2020)
Abstract Background Semen Ziziphi spinosae and Radix Polygalae, two herbs commonly used together in Traditional Chinese Medicine for the treatment of insomnia and anxiety. The study aims to study the sedative-hypnotic effect of the active components of the herbal pair, the possible mechanisms of such effect, and related metabolic pathways in vivo. Methods The sedative and hypnotic effect of the active components (EI30) of the herbal pair was studied by recording influence on the proportion of sleeping within 30 min, sleep latency and sleep length of pentobarbital sodium-induced sleeping on mice. Possible mechanisms of the sedative-hypnotic effect of the active components were investigated by measuring the content of neurotransmitters in the total protein of mice brain tissue. The main chemical compounds of the herbal pair were identified by Liquid Chromatography-Mass Spectrometry (LC-MS). Serum samples of mice were studied, and related differential metabolites between the normal group and model group, and between model group and treatment group were identified by Gas Chromatography Time-Of-Flight Mass Spectrometry (GC-TOF-MS), Principal Components Analysis (PCA), and Orthogonal Projections to Latent Structures Discriminant Analysis (OPLS-DA). Results Compared with the control group, high dose EI30 group and the Clonazepam group were with significantly higher proportions of sleep within 30 min (P = 0.027 and 0.005 respectively). Compared with the control group, all of the high, medium and low dose of EI30 groups were with significantly shorter sleep latency (P < 0.01) and prolonged sleeping time (P < 0.01). The herbal pair has good sedative-hypnotic effects, although it is weaker than the effect of Clonazepam. The sedative-hypnotic effect of EI30 is possibly related to the adjustment of neurotransmitters 5-hydroxytryptamine (5-HT), norepinephrine (NE), and dopamine (DA) in the total protein of mice brain tissue. There are five metabolic pathways in vivo most related to the sedative-hypnotic effect of EI30, and they are biosynthesis of valine, leucine, and isoleucine, metabolism of glyceride, metabolism of alanine, aspartic acid and glutamic acid, metabolism of phenylalanine, and metabolism of cysteine and methionine. Conclusions This study reveals the mechanisms of sedative and hypnotic effects of herbal pair Semen Ziziphi spinosae and Radix Polygalae by using metabolomics methods. This study provides a basis for further development and utilization of this herbal pair.